Evaluation of the likelihood of a selective CHK1 inhibitor (LY2603618) to inhibit CYP2D6 with desipramine as a probe substrate in cancer patients. (14th November 2014) - Hynes, Scott M.; Wickremsinhe, Enaksha; Zhang, Wei; Decker, Rodney; Ott, Jennifer; Chandler, Jason; Mitchell, Malcolm
Abstract LY2603618 is a selective inhibitor of deoxyribonucleic acid damage checkpoint kinase 1 (CHK1) and has been in development for the enhancement of chemotherapeutic agents. The study described was to assess the potential interaction between LY2603618 and cytochrome P450 isoform 2D6 (CYP2D6) substrate desipramine in patients with cancer. Before clinical investigation, in silico simulations (using Simcyp®) were conducted. An open‐label, two‐period, fixed‐sequence study was planned in 30 patients with advanced or metastatic cancers, in which a 50 mg oral dose of desipramine was administered alone and in combination with 275 mg of LY2603618 (i.v. infusion). An interim analysis was planned after 15 patients completed both periods. Ratios of geometric least squares means (LSMs) of primary pharmacokinetic (PK) parameters and 90% repeated confidence intervals (RCIs) between desipramine plus LY2603618 and desipramine alone were calculated. Lack of an interaction was declared if the 90% RCI fell between 0.8 and 1.25. The LSM ratios (90% RCI) for areas under the plasma concentration–time curve from time zero to tlast (AUC[0‐tlast]) and to infinity (AUC[0‐∞]) and maximum plasma concentration (Cmax) were 1.14 (1.04, 1.25), 1.09 (0.99, 1.21) and 1.16 (1.05, 1.29). In silico simulations were predictive of clinical results. Single doses of 275 mg LY2603618 administered with 50 mg desipramine were generally well tolerated. In conclusion, no clinically significant interaction was observed between LY2603618 and desipramine in patients with cancer. In silico predictions of clinical results demonstrated that mechanistic and physiologically based PK approaches may inform clinical study design in cancer patients. Copyright © 2014 John Wiley & Sons, Ltd.